2017
DOI: 10.1080/09593985.2017.1318422
|View full text |Cite
|
Sign up to set email alerts
|

Movement control tests for the lumbopelvic complex. Are these tests reliable and valid?

Abstract: This study evaluated inter- and intra-observer reliability and discriminative validity of three movement control tests: 1) standing knee-lift test; 2) static lunge test; and 3) dynamic lunge test. Thirty-eight subjects, 21 with low-back pain and 17 healthy, were video-recorded while performing the tests. Four physical therapists scored the tests according to a standardized protocol and calculated a composite score for each test based on the number of incorrect test components. Inter-observer reliability for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Several studies have demonstrated a link between musculoskeletal disorders, pain and the ability to adequately control movements and muscular activation in clinical tests (Hodges & Richardson, 1996; Luomajoki et al, 2008; Moseley & Hodges, 2006). Dynamic movement tests are gaining popularity as components of musculoskeletal screening with the goal of identifying increased injury risk (Granstrom, Ang & Rasmussen-Barr, 2017). According to Barbado et al (2016) perturbations of trunk movement can vary in amplitude and can range from self-imposed and predictable to externally imposed and unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a link between musculoskeletal disorders, pain and the ability to adequately control movements and muscular activation in clinical tests (Hodges & Richardson, 1996; Luomajoki et al, 2008; Moseley & Hodges, 2006). Dynamic movement tests are gaining popularity as components of musculoskeletal screening with the goal of identifying increased injury risk (Granstrom, Ang & Rasmussen-Barr, 2017). According to Barbado et al (2016) perturbations of trunk movement can vary in amplitude and can range from self-imposed and predictable to externally imposed and unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…The steps related to the selection of articles are outlined in the flow-diagram below (Figure 1). Of the 13 studies included, 10 investigated inter-rater reliability [28,29,30,31,32,33,34,35,36,37], 4 investigated intra-rater reliability [31,32,33,38], and only 6 studies analyzed validity [28,29,31,32,39,40]. Overall, the tests showed reliability ranging from fair to excellent ( K value between 0.32 and 1.00) for the inter-rater and from moderate to excellent for the intra-rater ( K value from 0.42 to 1.00).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen tests were investigated by a single author [28,30,31,32,33,36,37]. In the remaining 6 evaluated by multiple studies, only 4 (waiter’s bow, one leg stance, sitting knee extension, and prone hip extension) showed agreement between reliability values [29,33,34,36], while for the other 2 (bent knee fall out and active straight leg raising), this did not happen [29,30,33,35,36,37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations